Pembaharuan Metode Pembelajaran pada Mata Pelajaran Biologi Di MA Assholach pada Era Pasca Pandemi - Ni'mah, Ainun; Lailiyah, Nur; Adawiyah, Robi'atul; Airani, Kharisma Tri (FKIP Universitas Wisnuwardhana, 2023)
Madrasah Aliyah Assholach is one of the institutions under the auspices of the Pondok Pesanten Assholach Kejeron Foundation. Madrasah Aliyah Assholach was born in 2006 and has successfully graduated most of its students for further studies to private universities and state universities. Madrasah Aliyah Assholach Kejeron Gondang Wetan is the most popular superior educational institution. The purpose of this observation is to find out information about the renewal of learning methods in biology subjects at Madrasah Aliyah Assholach. This research method uses qualitative methods by conducting direct field observations by interviewing one of the teachers at Madrasah Aliyah Assholach to get complete information about the renewal of biology learning methods carried out at Madrasah Aliyah Assholach Kejeron. The renewal of methods in biology subjects at Madrasah Aliyah Assholach is only carried out in class X because only class X uses an independent curriculum with additional physics and chemistry biology maps with the addition of this mapel it is hoped that there will also be additional science majors in the following year. The renewal of this learning method is done by utilizing existing media and learning in real terms not only students listen and the teacher explains.